La Comprensión Lectora en el desarrollo del pensamiento crítico de los niños de tercero de Básica de la Escuela Fiscal Mixta Boyacá de la Parroquia San Gerardo, Cantón Guano, Provincia de Chimborazo, año 2014-2015 - Román Pérez, Mirian Inés (2016)
The aim of this research work allowed to analyze and raise the issue, where both general and specific objectives were made to be reached, the justification of the subject was conducted scíentifically and theoretically substantiated where the two variables studied where cleared, concluding critical thinking plays an important role in Brunner life which requires from the teacher the proper use of methodological strategies in Reading comprehension and to make it a use ful and enjoyable work. The re are many activities that help children from third grade to read better, for instance listening, questicoing, observing, singing, drawing and writing. So they develop their memory, reflection and imagination. Responding to this difficulty and making students expand the basic strategies for the proper development of critical thinking in reading comprebension, essential for the apprehension of all study área and of life it was decided to implement this project. Where the main beneficiaries with the result of our research were teachers and students from third grade of the Public School Boyacá, besides the research hypothesis was raised, then the research methodology that was deductive, inductive and analytical took place, descriptive and correlational research desing, literature field, the same that allowed us to research the theme, it was made the observation sheet from the children where it was analyzed and Interpreted the results and finally the conclusions are made and recommendations based on the specific objectives.